Makna Ritus “Teing Tinu” Masyarakat Manggarai dan Praktik Xiao (孝) dalam Pemikiran Confucius: The Meaning of the Manggarai People's "Teing Tinu" Rite and the Practice of Xiao (孝) in Confucian Thought - Hamat, Yulianus Evantus; Lie, Agustinus (Jurnal Filsafat Indonesia, 2024)
The main focus of this paper is to explore the philosophical values embedded in the "teing tinu" ritual of the Manggarai community, elaborated through the practice of Xiao (孝) in Confucian teachings. The teing tinu ritual signifies the responsibility of children towards their elderly parents. Additionally, this ritual serves as an expression of filial devotion, respect, and gratitude of children towards their parents for all the kindness and services rendered throughout their lives. It stands as a local wisdom that needs to be understood and acknowledged by the younger generation. Unfortunately, this expectation seems to be fading due to the younger generation's lack of attention to the teing tinu ritual, influenced by the rapid advancement of technology. The pragmatic and indifferent attitude of the younger generation in Manggarai has led to the erosion of the meaning and values inherent in the teing tinu ritual. Conversely, the prevalence of a culture of violence, rudeness, quick-triggered emotions, and social anarchy is beginning to permeate the lives of the younger generation in Manggarai. Amidst the challenges of life and the unstoppable flow of time, the author feels compelled to delve into and attempt to extract the meaning and values within Manggarai culture, particularly the teing tinu culture, as an effort to rekindle the adherence of the younger Manggarai generation to the prevailing norms of respect and courtesy. The author employs a literature review method and critical readings of Manggarai culture and Confucius' works, specifically focusing on the practice of Xiao in his writings. This research finds that various values in the teing tinu ritual are closely related to the values in the Xiao practice of Confucian teachings.